The relationships of mindfulness, gratitude and risk-based decision making among undergraduate students - Azlan, Amirah Zulaikha Zafrul (2022)
Risk-based decision making refers to a process that usually ensures optimal choices are chosen and are in line with the goals and perceptions of those concerned. People tend to use inaccurate information to make their decisions quickly. Past research found mindfulness and gratitude led individuals to become reluctant to take higher risks. It was highlighted in many of the limitations that studies did not look at student groups despite being at risk of making rash decisions considering they are at the starting stage for their development and career growth. Therefore, this study aims to examine the relationships between mindfulness, gratitude and risk-based decision making among undergraduate students. Undergraduate students (N = 164) from the School of Health Sciences, Medical Sciences and Dental Sciences, Universiti Sains Malaysia (USM) were recruited for this cross-sectional survey study. The Mindfulness Attention Awareness Scale (MAAS), Gratitude Questionnaire-Six-Item Form (GQ-6) and Domain-Specific Risk-Taking (DOSPERT) Questionnaires were used. The data was analysed using Linear Regression and Multiple Linear Regression. Results showed no relationship between mindfulness and risk-based decision making and a significant relationship between gratitude and risk-based decision making among students. Overall, the findings suggest that students with a higher level of gratitude would make lesser risk-based decisions. Mindfulness showing no relationship with risk-based decisions could be due to the field of studies of the students, related to the health. They may have been frequently exposed to risk-based decision during treatment planning of their patients, limiting mindfulness. To conclude, the study offers a further understanding of the need to advocate the practicality of being grateful, such as implementing skills training or therapeutic programs to reduce making risky decisions.